2021
DOI: 10.1002/edm2.315
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity, type 2 diabetes, and hyperglycaemia: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…This finding is similar to what has been previously reported by Beltr an et al for FIS and self-reported diabetes and hypertension. 78,83 It is currently unclear why foodinsecure patients are more likely to report such chronic diagnoses, although 1 possibility is a complex interaction between FIS, anxiety/depression, 31 and the odds of self-reporting poor health. 84 With respect to its clinical implications, our data do not indicate an association between FIS and dyslipidemia and thus do not support routine lipid screening of food-insecure individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to what has been previously reported by Beltr an et al for FIS and self-reported diabetes and hypertension. 78,83 It is currently unclear why foodinsecure patients are more likely to report such chronic diagnoses, although 1 possibility is a complex interaction between FIS, anxiety/depression, 31 and the odds of self-reporting poor health. 84 With respect to its clinical implications, our data do not indicate an association between FIS and dyslipidemia and thus do not support routine lipid screening of food-insecure individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study by Abdurahman et al further strengthens the hypothesis for an association between household food insecurity and increased risk of type 2 diabetes, with an odds ratio value of 1.27 (95% CI 1.11–1.42) [ 30 ]. Based on the studies mentioned previously, it appears that food insecurity is associated with different stages of diabetes mellitus; however, there are some recent studies that contrast the findings and do not suggest an association between food insecurity and clinically determined type 2 diabetes or significant differences in fasting blood glucose and HbA1c [ 31 ]. Beltran et al additionally stated that food insecurity is a complex issue and it might look different depending on factors such as social, economic, and geographic consideration [ 31 ].…”
Section: Food Insecurity and Risk For Diet-related Chronic Diseasementioning
confidence: 99%
“…Based on the studies mentioned previously, it appears that food insecurity is associated with different stages of diabetes mellitus; however, there are some recent studies that contrast the findings and do not suggest an association between food insecurity and clinically determined type 2 diabetes or significant differences in fasting blood glucose and HbA1c [ 31 ]. Beltran et al additionally stated that food insecurity is a complex issue and it might look different depending on factors such as social, economic, and geographic consideration [ 31 ]. The study explained that the differences in the findings might be a result of the difference in food insecurity concepts, where in some cases hunger and chronic starvation are the primary drives of food insecurity [ 31 ].…”
Section: Food Insecurity and Risk For Diet-related Chronic Diseasementioning
confidence: 99%
See 2 more Smart Citations